The role of Rezūm ™ team ablation of the prostate in the treatment of patients with acute urinary retention secondary to benign prostatic hyperplasia. A single center, single surgeon case series and literature review. (4th December 2020) - Wong, Anton; Mahmalji, Wasim
Abstract: Objectives: Acute urinary retention (AUR) is one of the most significant complication of benign prostatic hyperplasia (BPH). The gold standard surgical treatment for BPH, transurethral resection of the prostate (TURP), is not without significant side effects and a prolonged hospital stay. The aim of this study is to evaluate the role of Rezūm ™ steam ablation in the treatment of patients with AUR secondary to BPH. Methods: Patients who developed AUR and failed their trial without a catheter (TWOC) were recruited. They were counselled about the procedure and offered the treatment. Pre-operative, intraoperative and post operate data were collected. Results: All patients were followed up for a mean period of 7.2 months. 100% of patients passed their TWOC and stopped taking any BPH medications after. There was an average of 43.8% decrease in TRUS volume and a fall of 52.5% in PSA value after intervention. The mean operation time was 8.8 min and mean duration in hospital was 5.8 h. No deterioration in sexual function was reported. Conclusions: Rezūm ™ steam ablation of the prostate is safe, fast and effective day case procedure in treating patients with AUR secondary to BPH. All patients were satisfied with the functional outcomes.